The effectiveness of the protective role of beetroot juice for the male reproductive system of albino rats against the toxicity of cadmium chloride - Qasim Azeez Razooqi AL-Janabi; Rashid Khamees Shaban; Noor Ibrahem Hasan AL-Kraie (Tikrit Journal of Pure Science)
This study was designed to evaluate the protective role of beetroot juice against the toxicity of cadmium chloride (CdCl2) in male albino rats.